(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, taxation of land resources is an important component of the financial policy of economic development and formation of environmental stability. He studies the legal bases regulating the taxation of land resources in our country. By examining key legislation, regulations and policies, the abstract provides an overview of the legal framework governing the assessment and administration of land tax. In addition, he touches on the role of local authorities in land taxation, emphasizing their independence in adapting tax policies to regional needs. Mutual cooperation of central and local authorities in the distribution of land revenue is important in maintaining fiscal balance and ensuring fair distribution of resources.